Etiopathogenesis in Neuropsychological Aspects of Mood Disorders and Self-Harming Behavior in Adolescents: A Review - Mayumi Agestia; Fathul Djannah (Postgraduate, University of Mataram, 2024)
The average prevalence of self-harm in school-age adolescents in the world is 17.20% with bipolar spectrum disorders (37%) apparently higher than among adolescents with depressive disorders (13%). Based on etiopathogenesis, neuropsychological factors are associated with the emergence of mood disorders and self-harm behavior. The method used is the preparation of this article review was carried out through the process of searching, collecting data, and analyzing several articles from Science Direct, Proquest, Pubmed, and Google Scholar. The extracted data were analyzed to summarize the findings related to the etiopathogenesis of mood disorders and self-harm behavior in adolescents reviewed from a neurophysiological aspect. Discussion: Based on the results of the analysis of several articles, the etiopathogenesis of mood disorders and self-harm behavior in adolescents reviewed from a neurophysiological aspect is related to the influence of neurotransmitters and changes in the functional structure of the brain. The related neurotransmitters are serotonin, dopamine, GABA, glutamate, norepinephrine, and histamine. In adolescents who are not accompanied by psychological maturity, it can cause conflicts that result in emotional stress and distress as well as the emergence of negative emotions related to changes in brain function and structure related to brain neuroplasticity and disruption of the reward and punishment system in the limbic system.